Analisis Teori Offense-Defense Pada Reformasi Kebijakan Pertahanan Jepang Dalam Dinamika Keamanan Di Asia Timur - Alghifari, Fadhil; Letticia, Raja Nathania Olga (UI Scholars Hub, 2016)
This paper will seek to demonstrate how the use of Offense-Defense Theory can best explain the Japan’s new defense reform legislation that enables the country to play a more comprehensive global security role commensurate with its capabilities, resources, national interests, and international responsibilities. Through this offense-defense lens, it will be argued that Japan’s new defense reform legislation is a response to the growing dominance of ‘offensive’ behaviour by the neighbouring countries in East Asia. This paper will then elaborate more about the elements that are used in the offense-defense theory to analyze the ‘offense’ dominance that prompts East Asian states behave aggressively and defensively including Japan. Furthermore, this paper will explain why Japan is currently playing the ‘defensive’ role to counter the growing dominance of ‘offense’ in East Asia through the four variables of offense-defense balance; military doctrine and technology, geographical considerations, social and political order, and diplomatic arrangements. Thus, we will see that Japan holds the key to the offense-defense and security balance in the increasingly hostile environment in East Asia.